Varieties of accountability: How attributes of policy fields shape parliamentary oversight. Issue 1 (21st April 2017) - Bundi, Pirmin
Abstract : This article demonstrates how attributes of policy fields shape parliamentary oversight across policy fields. Building on the accountability literature, the study develops the argument that parliamentarians will more likely oversee policy fields where cooperative forms of governance are more present, since these policies are more difficult to assess and have a higher need of legitimation. Using the example of policy evaluation demand by members of parliament in Switzerland, the study suggests that parliamentarians seek more control in a policy field, where public activities are more often delegated to nopublic actors or the need for legitimation is particularly high. Both effects increase with the policy field's closeness to science. These findings could be very relevant in order to understand how attributes of policy fields shape political institutions.